IMPLEMENTASI STRATEGI MARKETING MIX 4P DALAM MENCIPTAKAN CUSTOMER LOYALTY PADA USAHA KURNIA MADU KEDIRI - Masrida, Lastik Putri Wiwin; Kusumaningtyas, Dian; Damayanti, Susi (Universitas Nusantara PGRI Kediri, 2023)
A sustainable marketing strategy becoming a significant trend. Constraints regarding the development of marketing strategies resulted in customer loyalty not being maximized, there were many competitors which became a phenomenon that was directly felt by Kurnia Madu Kediri Business. This study aims to determine the application of the right marketing mix in the Kurnia Madu Kediri Business as a strategy to create customer loyalty. A qualitative approach to this type of descriptive research is used as the research technique this time. Data collection techniques through interviews, observation, and documentation. The results of the study: 1) Kurnia Madu Kediri's business applies the 4P marketing mix strategy of product, price, promotion, and place. 2) Kurnia Madu Kediri business has carried out a good marketing strategy in terms of products by maintaining product quality and interesting innovations. Set the price according to the quality of honey offered. Has a strategic distribution location. Promotion through direct selling with very good and responsive communication, then it can be maximized in carrying out promotions online.